Peace in world history - Stearns, Peter N. (New York Routledge, 2014)
"In Peace in World History, Peter N. Stearns examines the ideas of peace that have existed throughout history, and how societies have sought to put them into practice. Beginning with the status of peace in early hunter-gatherer and agricultural societies, and continuing through the present day, the narrative gives students a clear view of the ways people across the world have understood and striven to achieve peace throughout history. Topics covered include: Comparison of the 'pax Romana' and 'pax Sinica' of Rome and China, concepts of peace in Buddhism, Christianity, and Islam, and their historical impact, the place of peace in the periods of expanding empires, the emergence, starting in the 19th century, of formal schemes to promote peace amid increasingly destructive technologies for warfare. Moving away from the view of history as a series of military conflicts, Peace in World History offers a new way of looking at world history by focusing on peace. Showing how concepts of peace have evolved over time even as they have been challenged by war and conflict, this lively and engaging narrative enables students to consider peace as a human possibility"--
Introduction -- Peace and early human societies -- The great empires : peace in Rome and China -- Peace in the Buddhist tradition -- Religion and peace in the postclassical age -- Peace in a new age of empires -- Peace in an industrial age -- Peace in the decades of war -- Peace in contemporary world history -- Regional approaches to peace : the comparative challenge -- Peace ideas and peace movements after 1945.
Includes bibliographical references and index.
Keywords: World history; Peace; HISTORY / World; HISTORY / Civilization; HISTORY / Social History